The Process of Implemented Audio-Lingual Method in Students' Listening Skill at SMA Negeri 3 Tana Toraja - Teresia Octavia Kala'allo; A. Muliati; Fatimah Hidayahni Amin (International Journal of Language, Education, and Literature, 2025)
This study examines the process of implementing the audio-lingual method to improve students’ listening skills at SMA Negeri 3 Tana Toraja. tarting from initial observations regarding students' challenges in understanding oral information, especially in a foreign language, this study aims to describe in depth how the audio-lingual method is implemented in the classroom and how its implementation affects students' listening skills. Using a qualitative approach with a case study, this study involved several students and English teachers at SMA Negeri 3 Tana Toraja as participants. Data were collected through in-depth interviews, participant observations in the classroom, and document analysis, including lesson plans and audio recordings of learning. The case study approach allows for contextual and in-depth exploration of phenomena, providing a comprehensive understanding of the dynamics of teacher-student interactions and students' responses to the methods applied. The results showed that the implementation of the audio-lingual method at SMA Negeri 3 Tana Toraja involved a series of structured activities such as repetition of sentence patterns, dialogues, and Drill exercises. Teachers consistently used audio recordings and emphasized correct pronunciation. However, challenges such as time constraints, large class sizes, and lack of variety of audio materials were also identified. These findings indicate that the audio-lingual method has great potential in improving students' listening skills through intensive and repeated exposure, but its effectiveness is highly dependent on contextual adaptation and teacher creativity in managing learning. This study is expected to provide valuable input for education practitioners in designing more effective language learning strategies, especially in developing students' listening skills.